2013
DOI: 10.1371/journal.pone.0080762
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a Human Endogenous Retrovirus Envelope-Coated, Nonreplicable, Baculovirus-Based Hemagglutin Vaccine against Pandemic Influenza H1N1 2009

Abstract: Despite the advantages of DNA vaccines, overcoming their lower efficacy relative to that of conventional vaccines remains a challenge. Here, we constructed a human endogenous retrovirus (HERV) envelope-coated, nonreplicable, baculovirus-based HA vaccine against swine influenza A/California/04/2009(H1N1) hemagglutin (HA) (AcHERV-sH1N1-HA) as an alternative to conventional vaccines and evaluated its efficacy in two strains of mice, BALB/c and C57BL/6. A commercially available, killed virus vaccine was used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Although aluminum-adjuvanted inactivated split-virion 2009 pandemic influenza A H1N1 vaccine provides long-term protection against lethal influenza virus challenge in mice after a single immunization, as shown in this study, various other forms of influenza vaccine have also been developed and reported (20)(21)(22). Giles et al reported that mice were immunized with influenza virus-like particles (VLPs) expressing the hemagglutinin (HA) and genes from the 1918 influenza virus, and the results showed that 3 g of purified 1918 VLPs protected mice from 2009 pandemic H1N1 virus challenge 16 months after double vaccination via intramuscular injection at 0 and 3 weeks (20).…”
Section: Discussionmentioning
confidence: 88%
“…Although aluminum-adjuvanted inactivated split-virion 2009 pandemic influenza A H1N1 vaccine provides long-term protection against lethal influenza virus challenge in mice after a single immunization, as shown in this study, various other forms of influenza vaccine have also been developed and reported (20)(21)(22). Giles et al reported that mice were immunized with influenza virus-like particles (VLPs) expressing the hemagglutinin (HA) and genes from the 1918 influenza virus, and the results showed that 3 g of purified 1918 VLPs protected mice from 2009 pandemic H1N1 virus challenge 16 months after double vaccination via intramuscular injection at 0 and 3 weeks (20).…”
Section: Discussionmentioning
confidence: 88%
“…Although 2 μg of killed vaccine has been reported to elicit a sufficient immune response and afford protection [ 21 ], an adjuvant is expected reduce the quantity of antigen needed for effective immunization. Thus, in preliminary experiments to evaluate the efficacy of AcHERV-GmCSF, we determined the minimum necessary dose of killed vaccine for use in conjunction with AcHERV-GmCSF.…”
Section: Resultsmentioning
confidence: 99%
“…A recombinant baculoviral vector expressing HERV env (pFastBac1-HERV) was previously constructed by inserting a synthetic, codon-optimized envelope gene of HERV type W (GenBank accession number NM014590; GenScript, Piscataway, NJ, USA) into pFastBac1 (Invitrogen) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…These attributes have fueled interest in exploring baculoviruses as vectors for recombinant protein expression systems and gene therapy [ 18 20 ]. In spite of the advantages of baculovirus, overcoming their lower efficacy relative to that of conventional vaccines remains a challenge [ 21 ]. We previously reported that a non-replicable baculovirus vector containing antigen-encoding DNA could serve as a nano-delivery system, and improve exogenous gene delivery into human cells by incorporating the envelope glycoprotein of human endogenous retrovirus (HERV-W) on recombinant baculovirus [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the AcHERV-HA vaccine only elicited an immune response to HA proteins. Such monovalency may limit the degree of protection against heterologous influenza viruses [ 21 ]. Here, we constructed a baculovirus carrying pH1N1 HA, NA, and M1 genes that is able to assemble VLPs in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%